AUTOMATED SYSTEM OF ANALYSIS AND RECOGNITION OF VENTRICULOGRAMS ON THE BASE OF REPAGULAR WAVELET TRANSFORM - Polyakova, Marina; Krylov, Victor; Gulyaeva, Natalia; Pruschak, Tatyana (International Journal of Computing, 2010)
The method of the extraction of the left ventricle contours is developed for ventriculograms which obtained by radiological research of heart with the angiographic system. The proposed method includes the underlining of left ventricle contours through the repagular wavelet transform, that allows to reduce the error of detection of the edge and the area of left ventricle.